Efficacy of montelukast in allergic rhinitis Treatment: A systematic review and meta-analysis - Krishna Moorthy, Madhusudhan (2020)
In treating allergic rhinitis (AR), montelukast has the potential to be used as an alternative or addition to oral antihistamine (OAH) or intranasal corticosteroid. Objectives: To assess the effectiveness of montelukast in treating AR. Methods: An electronic literature search was performed using Cochrane Central Register of Controlled Trials, EMBASE and MEDLINE from 1966 to 21st January 2019. The eligibility criteria were randomized control trials comparing montelukast with placebo or other standard treatments. The primary outcomes assessed were daytime nasal symptom score (DNS) and nighttime nasal symptom score (NNS). The secondary outcomes assessed were composite nasal symptom score (CSS), daytime eyes symptom score (DES) and rhinoconjunctivitis quality of life questionnaires (RQLQ). Meta-analysis was done using Review Manager 5.3 software based on the random-effects model. Results: Fifteen studies of 10387 participants met the inclusion criteria. Montelukast was effective than placebo in improving DNS (MD -0.12, 95% CI -0.15 to -0.08; P < 0.001), NNS (MD -0.09, 95% CI -0.13 to -0.05; P < 0.001), CSS (MD -0.08, 95% CI -0.11 to -0.06; P < 0.001), DES (MD -0.17, 95% CI -0.33 to -0.02; P < 0.030) and RQLQ (MD -0.34, 95% CI - 0.49 to -0.20; P < 0.001). OAH was superior than montelukast in improving DNS (MD 0.08, 95% CI 0.03 to 0.13; P=0.002), CSS (MD 0.03, 95% CI -0.02 to 0.07; P=0.270), DES (MD 0.06, 95% CI 0 to 0.12; P=0.040) and RQLQ (MD 0.03, 95% CI -0.05 to 0.12; P=0.430). Montelukast was superior than OAH in improving NNS (MD -0.03, 95% CI -0.08 to 0.03; P=0.330). Intranasal fluticasone spray was superior than montelukast in improving DNS (MD 0.71, 95% CI 0.44 to 0.99; P < 0.001) and NNS (MD 0.63, 95% CI 0.29 to 0.97; P < 0.001). A combined montelukast and OAH was superior than OAH in in improving DNS vii (MD -0.15, 95% CI -0.27 to -0.03; P =0.010), NNS (MD -0.16, 95% CI -0.28 to -0.05; P =0.006), CSS (MD -0.12, 95% CI -0.25 to -0.01; P =0.070), DES (MD -0.12, 95% CI -0.30 to 0.06; P =0.180) and RQLQ (MD -0.10, 95% CI -0.28 to 0.08; P =0.290). A combined montelukast and OAH was superior than montelukast improving DNS (MD 0.15, 95% CI 0.08 to 0.21; P<0.001), NNS (MD 0.05, 95% CI -0.09 to 0.19; P=0.510), CSS (MD 0.1, 95% CI 0.03 to 0.17; P=0.007), DES (MD 0.18, 95% CI 0 to 0.36; P=0.050) and RQLQ (MD 0.07 95% CI -0.15 to 0.29; P=0.530). Conclusion: Montelukast is effective in treating AR patients with nocturnal symptoms and as add on combination therapy with OAH in the stepping up management of AR.